Genetic diversity and population structure of Solea solea and Solea senegalensis and its relationships with life history patterns - Teixeira, Tatiana Fonseca de Araújo (2010)
Tese de mestrado em Biologia e Gestão dos Recursos Marinhos , apresentada à Universidade de Lisboa, através da Faculdadede Ciências, 2007